2019
DOI: 10.3389/fpsyg.2019.00543
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adolescent Depression: A Review of Theories, Evaluation Instruments, Prevention Programs, and Treatments

Abstract: Depression is the principal cause of illness and disability in the world. Studies charting the prevalence of depression among children and adolescents report high percentages of youngsters in both groups with depressive symptoms. This review analyzes the construct and explanatory theories of depression and offers a succinct overview of the main evaluation instruments used to measure this disorder in children and adolescents, as well as the prevention programs developed for the school environment and the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(145 citation statements)
references
References 180 publications
(162 reference statements)
5
122
1
17
Order By: Relevance
“…Adolescents are particularly vulnerable to developing mental health problems, and the majority of mental health problems develop during adolescence (Patel, Flisher, Hetrick, & McGorry, 2007). Depression in adolescence is associated with several factors including hormonal and neurobiological changes, negative family relationships, and bullying from peers (Bernaras, Jaureguizar, & Garaigordobil, 2019;Storr, Pacek, & Martins, 2012;Thapar, Collishaw, Pine, & Thapar, 2012). Substance use is typically initiated during adolescence (Johnston, O'Malley, Bachman, & Schulenberg, 2012) and has been shown to be prevalent in adolescents across multiple countries (Mutumba & Schulenberg, 2019).…”
Section: Depressive Symptoms and Substance Usementioning
confidence: 99%
“…Adolescents are particularly vulnerable to developing mental health problems, and the majority of mental health problems develop during adolescence (Patel, Flisher, Hetrick, & McGorry, 2007). Depression in adolescence is associated with several factors including hormonal and neurobiological changes, negative family relationships, and bullying from peers (Bernaras, Jaureguizar, & Garaigordobil, 2019;Storr, Pacek, & Martins, 2012;Thapar, Collishaw, Pine, & Thapar, 2012). Substance use is typically initiated during adolescence (Johnston, O'Malley, Bachman, & Schulenberg, 2012) and has been shown to be prevalent in adolescents across multiple countries (Mutumba & Schulenberg, 2019).…”
Section: Depressive Symptoms and Substance Usementioning
confidence: 99%
“…Recent studies made in healthy middle-aged women revealed that a daily consumption of a low-dose supplement containing bioavailable tryptophan may have beneficial effects on emotional and cognitive functions [10]. It is known that there are biological factors (such as tryptophan-a building block of serotonin-depletion) which strongly influence the appearance of depressive disorders [45]. Tryptophan hydroxylase-2 (TPH-2) gene may play an important role in maintaining the normal level of serotonin in the central nervous system [46,47], and, as suggested by Ping et al (2019) [17], neurotransmission by serotonin in the brain may be associated with changes in white matter integrity in patients with major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…According to the fifth edition of DSM, depressive disorders are categorized as major depressive disorder, dysthymic disorder, disruptive mood disorder, premenstrual dysphoric disorder, substance or drug related depressive disorder, depressive disorder due to a medical condition, and otherwise undifferentiated depressive disorder (5). With the system of ICD, the most commonly diagnosed depressive disorders are single depressive episode, recurrent depressive disorders, and persistent mood disorders (6). Depression is the most prevalent psychiatric disorder among general population (7).…”
Section: How Do We Recognize Depression?mentioning
confidence: 99%
“…Depression is the most prevalent psychiatric disorder among general population (7). The patients with depression often have low self-esteem, suffer overwhelming unwillingness, and are afflicted by attention and concentration deficits which result in cognitive impairments (6,8). Depression may exceed being an affective problem and lead to physical abnormalities.…”
Section: How Do We Recognize Depression?mentioning
confidence: 99%
See 1 more Smart Citation